PRINSIP-PRINSIP KONSTITUSIONALITAS KOPERASI BERDASARKAN UUD NEGARA RI TAHUN 1945 - Agus Kusnadi; Aan Eko Widiarto (Arena Hukum, 2016)
Abstract Cooperative identity is at risk with the Act 17 of 2012 on Cooperatives, which relies on the values of capitalism. Capitalism is characterized through the economic activities and financial control by the efforts of large private properies in the sense of the individual and groups, profit oriented, the market economy competition dominant supported by consumerism, and the pricing of labor that follows the market mechanism. As a result, it is importance to make purification of cooperative base on UUD 1945 as set in Art. 33 par. (1), to make clear the principles of constitutionality of cooperatives in Indonesia. The principle of the constitutionality of the cooperative include brotherhood, man as main actors, social welfare oriented, synergy, market driven, shared interests, and mutual interest.Â AbstrakJati diri koperasi terancam hilang dengan adanya UU 17 Tahun 2012 tentang Perkoperasian yang menyandarkan pada nilai-nilai kapitalisme. Kapitalisme dicirikan adanya kegiatan ekonomi dan kontrol keuangan oleh usaha-usaha besar milik privat dalam arti orang seorang maupun keluarga, akumulasi laba sebesar-besarnya dalam motif profit (profit oriented), ekonomi pasar persaingan dominan yang ditopang dengan konsumerisme, dan penentuan harga tenaga kerja yang mengikuti mekanisme pasar. Akibatnya diperlukan pemurnian bangun usaha koperasi sebagaimana UUD 1945 mengaturnya dalam Pasal 33 ayat (1) sehingga jelas prinsip-prinsip konstitusionalitas koperasi di Indonesia. Prinsip konstitusionalitas koperasi meliputi berasaskan kekeluargaan, manusia sebagai penentu, berorientasi pada kesejahteraan sosial, kerjasama/sinergi, pasar dikendalikan, kepentingan bersama, dan mutual interest.